By chance or providence ebook - Cloonan, Becky (Image Comics, 2018)
BY CHANCE OR PROVIDENCE collects BECKY CLOONAN's award-winning trilogy: WOLVES, THE MIRE, and DEMETER, with lush colors by LEE LOUGHRIDGE and a sketchbook/illustration section. These stories cast a spell of hypnotic melancholy, weaving their way through medieval landscapes of ancient curses and terrible truths that will haunt you long after you've set them down.. Author: Becky Cloonan. Illustrator: Becky Cloonan, Lee Loughridge . 2017 Becky Cloonan.